Impact of perceptions of bus service performance on mode choice preference. (16th March 2015) - Hu, Xiaojian; Zhao, Linna; Wang, Wei
As transit service performance should be considered from the transit passengers' perspectives, it is essential to determine passengers' perceptions of service performance and to understand the role of these perceptions in travel decisions. As the bus market share has steadily declined, the aim of this study is to explore the impact of perceptions of bus service performance on mode choice preference to increase bus ridership. To achieve this research objective, an intention survey is conducted to obtain bus passengers' attitudes. Exploratory factor analysis and confirmatory factor analysis are used to measure passengers' perceptions and to extract the main factors from the bus service attributes. Next, structural equation modeling is used to reveal how passengers' perceptions vary by demographics and trip characteristics. Finally, multinomial logit modeling is used to explore the impact of perception factors on mode choice preference. The results of this study show that perceptions of the reliability and comfort of bus services have a more significant impact on passengers' mode choice preference than perceptions of availability and safety do. The implications in terms of improving bus service reliability and comfort can increase bus ridership.